Pineapple farmers’ information sources and usage in Nigeria (2008)
Pineapple farmers’ access to and use of information have great income generation potentials for farmers, expansion of local industries and foreign exchange earnings for Nigeria This study, thus investigated farmers' information sources and usage. Interview schedule was used to collect data from 119 respondents which constituted 27% of all pineapple farmers in the study area. Results show respondents were mostly male (60%), married (66%), with one form of education or another (X = 3.09, SD = 1.46), and aged 28 years and above (71%). Relationships exist between respondents' selected personal characteristics and information sources and usage, years of farming and farming activities challenges. Pineapple farmers will source and use information from easily available and accessible sources such as radio and newspaper. Improving the knowledge base of farmers' will facilitate information sharing amongst them. Research and extension should therefore develop contents in both radio and newspapers that will expand farmers' knowledge base and practical skills for improved pineapple production.